Множинні слабкі спільні вимірювання як спосіб пригнічення декогеренції - Konovalenko, O.M.; Maizelis, Z.A. (Publishing house "Academperiodika", 2025)
We apply the multiple, equally spaced in time, weak measurements, to the two-qubit entangled system to decrease the rate of its decoherence, i.e., to prevent the decrease of the off-diagonal elements. The scheme is similar to the Quantum Zeno Effect, but differs by the frequency of the measurements. While the conventional Quantum Zeno Effect assumes rapid measurements which mitigates the Hamiltonian dynamics, the proposed method makes use of entanglement between the qubits to decrease the decoherence rate. We will show that it allows us to partially suppress the decoherence in the case of Lindblad evolution.